KKM Mentorship: Enhancing Elementary Students' Knowledge and Motivation in Ciputri Village, Pandeglang - Fanina Gustiawati; Putri Mutiah Agusina; Hesti Agustina; Nova Alin; Ganjar Sidik Gandara; Rahman Mulyana (Jurnal Pengabdian Cita Masyarakat, 2026)
The disparity in elementary educational quality within rural regions constitutes a systemic structural barrier to achieving national academic equity. At the micro level in Ciputri Village, students experience severe motivational stagnation and literacy deficits caused by inadequate infrastructure and minimal domestic oversight. Previous academic interventions were predominantly transactional, rigidly executed, and systematically ignored organic community participation and local cultural integration. This applied research aims to reconstruct an inclusive communal learning ecosystem by utilizing rigorous participatory methodologies. The intervention validates that deconstructing instructional hierarchies alongside implementing small group tutoring completely restored motivation, accelerated fundamental literacy, and eliminated language anxiety. The novelty fundamentally lies in deploying a comprehensive hybrid curriculum that precisely synthesizes modern cognitive competencies with affective dimensions through local arts and religiosity. These findings theoretically and practically guarantee a sociological consensus ensuring program ownership transfers, creating a sustainable rural educational empowerment framework thereby eliminating existing institutional limitations continuously and permanently.